W poszukiwaniu tożsamości – o roli bohaterów filmowych w kreowaniu aspiracji młodzieży - Myszka, Lucyna (Kultura-Społeczeństwo-Edukacja, 2016)
One of the main goals to be achieved by the youth concerns their attempts to form one's own identity. The participation in an ambiguous and ambivalent space of the contemporary reality produces various experiences, in all of which they are tying to find some helpful clues for creating the personal "self". Technological development and an increasing role of the graphic forms of information transmission in the sociocultural life oftentimes contribute to the employment of a generous and easily obtainable selection of motion pictures by the young. Those films tend to draw a spectator into the world of heroes who constantly succeed on the chosen path and continually fulfil their dreams. The main message being transmitted through many films towards the teenage receiver is simple: "you can be whoever you want to be – you just have to believe in yourself and start acting". That maxim makes the film characters' lifestyle highly desired by teenagers; the way of living displayed on the screen quite often becomes a source of their aspirations.